Can alanine aminotransferase measured in early pregnancy predict macrosomia?. (18th August 2022) - Bulut, Ayca Nazli; Ceyhan, Venhar; Dolanbay, Mehmet
Abstract: Non-alcoholic fatty liver disease (NAFLD) is a part of the metabolic syndrome and is associated with adverse pregnancy outcomes. The aim of this study was to determine whether unexplained elevated ALT in early pregnancy has any effect in the prediction of large for gestational age (LGA) infants. In this study, the relationship between birth weights of LGA babies and babies with normal weight for gestational age (AGA) and ALT values measured in early pregnancy was evaluated. While a positive, moderately strong, statistically significant correlation was found between infant birth weight and ALT levels in LGA babies this correlation was continued when GDM was not detected and ALT levels were below 36 U/L. Foetal macrosomia, which can develop in advanced gestational weeks, can be predicted with this cheap, easy and simple method that can be checked in the first trimester and pregnancy follow-up can be shaped accordingly. IMPACT STATEMENT: What is already known on this subject? It is suggested that asymptomatic high ALT values measured in the first trimester can predict a macrosomic foetus. What do the results of this study add? Asymptomatic elevated ALT values measured in the first trimester can predict a macrosomic foetus. What are the implications of these findings for clinical practice and/or further research? Macrosomic foetus development can be predicted with abnormal results obtained with this simple, cheap and easy measurement method measured in the first trimester and pregnancy follow-up can be managed accordingly.